2011
DOI: 10.1007/s11999-011-1910-2
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Rate of Irrigation and Débridement for Periprosthetic Joint Infection

Abstract: Background Irrigation and débridement with retention of prosthesis is commonly performed for periprosthetic joint infection. Infection control is reportedly dependent on timing of irrigation and débridement relative to the index procedure. Questions/purposes We therefore (1) compared the ability of irrigation and débridement to control acute postoperative, acute delayed, and chronic infections and (2) determined whether any patient-related factors influenced infection control. Patients and Methods We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 25 publications
8
131
1
6
Order By: Relevance
“…Acute postoperative PJI was diagnosed if infection occurred within 6 weeks of index primary joint arthroplasty [3]. Acute delayed PJI was diagnosed if onset of symptoms occurred abruptly in a previously well-functioning joint [9]. Chronic PJI was suspected when infection was diagnosed after 6 weeks from index primary joint arthroplasty with symptoms of persistent joint pain or discomfort since surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Acute postoperative PJI was diagnosed if infection occurred within 6 weeks of index primary joint arthroplasty [3]. Acute delayed PJI was diagnosed if onset of symptoms occurred abruptly in a previously well-functioning joint [9]. Chronic PJI was suspected when infection was diagnosed after 6 weeks from index primary joint arthroplasty with symptoms of persistent joint pain or discomfort since surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have indicated that regardless of the treatment modality, whether I&D [3,7] or one-stage [16] or two-stage exchange [17,19,21,36], infections caused by the more virulent organisms have a higher failure rate. Although our study was underpowered to draw definitive conclusions regarding implant retention based on organism, we are also concerned whether cementless single-stage exchange arthroplasty can control MRSA infection supporting prior authors' results [3,7,14,18] that these patients may best be treated with a two-stage exchange arthroplasty.…”
Section: Discussionmentioning
confidence: 51%
“…Although a number of publications have been described the outcomes of irrigation and débridement (I&D) with modular component exchange for periprosthetic joint infection (PJI) [1,3,7,8,13,15,18,20], the majority of published research on the topic has combined cohorts of patients (eg, hip versus knee and timing of infection) [3,18,22,31], thus making it difficult to tease out the differential success rates of the procedure for periprosthetic hip versus knee infection or type of infection (acute hematogenous versus chronic versus acute postoperative) ( Table 3). As well, it is likely that variations of defining treatment success, in this case component retention, contribute to the variation in reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations